The investigations of the electrical energy regime input influence on the kinetic parameters of the explosive electro-dynamic pinch-accelerator of mass - Sivkov A. A. Aleksandr Anatolyevich; Korolkov V. L.; Kovalenco A. N.; Novicov V. A. (1995, 1995)
В фонде НТБ ТПУ отсутствует